Snow leopards. - McCarthy, Thomas (Biologist); Mallon, David; Schwartz, Karin R. (Biodiversity of the world, 2023)
Snow Leopards, Second Edition provides a foundational, comprehensive overview of the biology, ecology and conservation of this iconic species. This updated edition incorporates all the recent information from range-wide surveys and conservation projects, the results of technical and advances particularly in genetics, camera trapping and satellite tracking, and evaluates emerging threats. New chapters synthesize the novel scientific methods and statistical analyses used to develop density and population estimates and how they inform conservation and management estimates. Sections cover historical information, the main biogeographic patterns, evolutionary trends, conservational efforts, and cultural significance. Status and distribution are fully updated for all 12 countries where snow leopards occur. Other sections describe established and emerging threats, including human-wildlife conflict, illegal trade, infrastructure development, and climate change along with conservation solutions used to address these threats. The book concludes with a final section on global snow leopard initiatives and future potentials.